STUDI KOMPARATIF PENDAPATAN USAHATANI PADI SAWAH SISTEM TANAM PINDAH DAN TANAM BENIH LANSUNG DI KECAMATAN MATAOLEO KABUPATEN BOMBANA - Rosmalah, Sitti; Hartati, Hartati; Hastian, Hastian; Harianti, Harianti; Nurmaya, Nurmaya (Agros Journal of Agriculture Science, 2024)
Efforts to use the right cultivation system are one of the intensification programs. The right cultivation system does not only concern the use of superior varieties, but also the selection of the right planting system. The direct seed planting system and the transplanting system are alternative planting systems introduced to farmers to increase production. These two planting systems have differences in terms of technical aspects and also the use of production factors so that specific studies related to both need to be carried out in order to find the most appropriate, effective and efficient planting system in increasing production and farm income. The purpose of this study was to analyze the differences in income and to conduct a difference test on the income of the tabela and tapin systems in Pomontoro Village, Mataoleo District, Bombana Regency. The results showed that the income of the tabela and tapin systems had significant differences based on the results of the difference test using SPSS. Key-words: income, tabela, tapin